ANALISIS PENGARUH SUMBER DAYA MANUSIA TERHADAP KEMISKINAN DI PROVINSI JAWA TENGAH - Titik Suhartini (Politeknik Sawunggalih Aji, 2018)
This study is to analyze the role of human resources to economic growth and its impact on poverty. The roleof human resources which are discussed are health, education, workforce, investment and entrepreneurship. The modelused in this study is based on the theory of neoclassical economics growth which are capital and labor factors. The dataused is the cross section from the 35 districts / cities in central Java and time series data for 5 years (2009-2013) by usingregression analysis with OLS (Ordinary Least Squares) with panel data. The estimation results show that the variables of health, labor, investment, entrepreneurship and education hada significant and negative effect to poverty, while the labor force had negative but not effect to poverty.